Oxygen consumption in the sandy beaches of the Vistula River: Goods and services of the ecosystem - Patrycja Słodownik; Krzysztof W. Opaliński (Studia Ecologiae et Bioethicae)
The research aimed to estimate the role of the beach in the process of self-purification of water in the Vistula River. The study could become a very important voice in the debate about the future of the Vistula River. A self-purification process involves the disposal of pollutants entering the water from the catchment of the River. A measure of the Vistula River water purification process of organic matter is the amount of oxygen that is consumed by the beach settlement. That is the amount of utilised organic matter by psammon during cellular respiration. Besides, the calculation of the amount of organic matter, which was worn by psammon can be the measure of “goods and services of the ecosystem” of the river.